The Relationship Between Postgraduates’ Emotional Intelligence and Well-Being: The Chain Mediating Effect of Social Support and Psychological Resilience - Shuo, Zhang; Xuyang, Deng; Xin, Zhao; Xuebin, Cai; Jie, Hou (Frontiers in Psychology, 2022)
Background: Postgraduates usually face more life challenges than undergraduate students, including social, emotional and financial issues, and the prevalence of mental health problems in postgraduates is higher than undergraduates. Therefore, the attention on postgraduates’ mental health status is needed. Objectives: The current study explored the relationship between postgraduates’ emotional intelligence and well-being by investigating the mediating effects of social support and psychological resilience and the relationship between them through the construction of a chain mediation model. Method: 1,228 postgraduates completed the Emotional Intelligence Scale, the Social Support Rate Scale, the Psychological Resilience Scale, and the Subject Well-being Scale. Results: There is a chain effect between postgraduates’ social support and psychological resilience mediated by their emotional intelligence and well-being, with a total effect value of 0.049. Conclusion: Emotional intelligence has a predictive effect on postgraduate well-being. The mechanism of this effect includes the indirect effects of social support and psychological resilience. Study results revealed the relationship mechanism between emotional intelligence and postgraduate well-being and provide reference for explorations of how-to development postgraduates’ emotional intelligence and further improving their abilities to strengthen their emotional resilience.